Heritabilities, genetic and phenotypic correlations between carcass and live animal traits in sheep - Menzies, C.S.; Wheat, J.D.; Mackintosh, D.L.; Kropf, Donald H. (Kansas Agricultural Experiment Station, 2011)
Data were collected on 94 lambs of known breeding born the fall of 1962. The lams were from ewes in the original fine-wool flock sired by eight unrelated Suffolk yearling rams. This was the ewes fourth lam crop.
Keywords: Sheep; Heritability; Genetic; Carcass characteristics